Aquaculture and the new problems of sea environmental protection from the international prespective - Łukaszuk, Leonard (Studia Ecologiae et Bioethicae, 2007)
The author shows in his work the analysis of five basic concepts from the range of hydrosphere in the context of historical and contemporary researches. Above all, the analysises concern the international law files, European Union, Poland and basic aspects of sea environmental protection: ecological aspect, economical aspect and law aspect.